Forecasting the Pandemic COVID-19 in India: A Mathematical Approach - Mandal, Manotosh; Jana, Soovoojeet; Majee, Suvankar; Khatua, Anupam; Kar, T. K. (Journal of Applied Nonlinear Dynamics, 2026)
Due to the unavailability of proper antiviral therapies and high disease transmission rates, the pandemic COVID-19 is still increasing at a high rate in many countries. In each of the three countries, the USA, Brazil, and India, the COVID-19 positive cases have been crossed one million. With high population density and higher percentages of migrating workers has enabled India to be vulnerable to the disease quite more than other affected countries. In this paper, we have proposed a mathematical model with the help of a system of first-order ordinary differential equations and analyzed the model in the context of the COVID-19 pandemic. We have determined the expression of the basic reproduction number and relates it to establishing the disease-free equilibrium point’s asymptotic stability and endemic equilibrium point. As it has been observed that only ten states and union territories are carrying more than 70% infection in India, we have predicted long-term scenarios of the COVID-19 positive cases on those 10 states and India until the end of the year 2020.